The X-ray emission in young radio active galactic nuclei. Issue 1 (4th June 2020) - Liao, Mai; Gu, Minfeng; Zhou, Minhua; Chen, Liang
ABSTRACT: In this work, we investigated the X-ray emission for a sample of young radio active galactic nuclei (AGNs) by combining data from Chandra / XMM–Newton with data for other wavebands. We find strong correlations between the X-ray luminosity L X at 2–10 keV and the radio luminosities L R at 5 GHz for the VLBI radio-core, VLA radio-core and Faint Images of the Radio Sky at Twenty-Centimeters (FIRST) component, indicating that both parsec- and kiloparsec-scale radio emissions are strongly correlated with X-ray emission in these sources. We find an approximately linear dependence of the radio on the X-ray luminosity in the sources with radiatively efficient accretion flows (i.e. the Eddington ratio R edd ≳ 10 −3 ), with b ∼ 1 ($L_{\rm R}\, \propto \, L_{\rm X} ^{b}$ ) and $ξ _{\rm RX}\, \sim$ 1 in the fundamental plane using the VLBI data. The dependence is consistent with the re-analysed results of a previous study of Fan and Bai at R edd ≳ 10 −3, but is significantly different from the theoretical prediction of accretion flow as the origin of X-ray emission. In contrast to the case for radio-quiet quasars, there is no significant correlation between Γ and the Eddington ratio. Our results seem to indicate that the X-ray emission of high-accretion young radio AGNs may be from the jet. We constructed the spectral energy distributions (SEDs) for 18 sources (most of which are in radiatively efficient accretion), namely nine galaxies and nine quasars with high-quality X-ray data, and find that the X-ray emission of most quasars is more luminous than that of normal radio-quiet quasars. This is clearly seen from the quasar composite SED, in which the X-ray emission is apparently higher than that of radio-quiet quasars, probably supporting jet-related X-ray emission in young radio AGNs. The possibility that the X-ray emission is from self-synchrotron Compton is discussed.